Litter stoichiometric traits of plant species of high-latitude ecosystems show high responsiveness to global change without causing strong variation in litter decomposition. - Aerts, R.; van Bodegom, P.M.; Cornelissen, J.H.C. (New Phytologist, 2012)
High-latitude ecosystems are important carbon accumulators, mainly as a result of low decomposition rates of litter and soil organic matter. We investigated whether global change impacts on litter decomposition rates are constrained by litter stoichiometry. • Thereto, we investigated the interspecific natural variation in litter stoichiometric traits (LSTs) in high-latitude ecosystems, and compared it with climate change-induced LST variation measured in the Meeting of Litters (MOL) experiment. This experiment includes leaf litters originating from 33 circumpolar and high-altitude global change experiments. Two-year decomposition rates of litters from these experiments were measured earlier in two common litter beds in sub-Arctic Sweden. • Response ratios of LSTs in plants of high-latitude ecosystems in the global change treatments showed a three-fold variation, and this was in the same range as the natural variation among species. However, response ratios of decomposition were about an order of magnitude lower than those of litter carbon/nitrogen ratios. • This implies that litter stoichiometry does not constrain the response of plant litter decomposition to global change. We suggest that responsiveness is rather constrained by the less responsive traits of the Plant Economics Spectrum of litter decomposability, such as lignin and dry matter content and specific leaf area. © 2012 The Authors New Phytologist © 2012 New Phytologist Trust.